2014
DOI: 10.1103/physrevb.90.081301
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing fine-structure splittings in telecommunication-wavelength quantum dots grown on (111)A surfaces by droplet epitaxy

Abstract: The emission cascade of a single quantum dot is a promising source of entangled photons. A prerequisite for this source is the use of a symmetric dot analogous to an atom in a vacuum, but the simultaneous achievement of structural symmetry and emission in a telecom band poses a challenge. Here we report the growth and characterization of highly symmetric InAs/InAlAs quantum dots self-assembled on C3v symmetric InP(111)A. The broad emission spectra cover the O (λ ∼ 1.3 µm), C (λ ∼ 1.55 µmm), and L (λ ∼ 1.6 µm) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 63 publications
(55 reference statements)
2
52
1
Order By: Relevance
“…Previous reports have shown a correlation between the emission wavelength and the FSS of the quantum dot for both SK dots [7] and DE dots [8]. However, for the DE QDs studied here, we observe no obvious correlation, as shown in Fig.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Previous reports have shown a correlation between the emission wavelength and the FSS of the quantum dot for both SK dots [7] and DE dots [8]. However, for the DE QDs studied here, we observe no obvious correlation, as shown in Fig.…”
Section: Discussioncontrasting
confidence: 52%
“…Production of quantum dots with naturally small FSS may be achieved in special cases, by self-assembled growth of InAs quantum dots around 885 nm, where an inversion of the wave-function symmetry is observed [7], or growth on (111) surfaces [8][9][10], aided by the underlying C 3v crystal symmetry which very often results in dot density preventing the spectral isolation of individual lines [11][12][13]. Another approach is the growth of strain-free GaAs=ðAl; GaÞAs QDs in locally etched pits [14].…”
Section: Introductionmentioning
confidence: 99%
“…2). While vanishing FSS of QDs grown along (111) direction is predicted theoretically 20,42,43 and typically small values were obtained experimentally, 21,44,45 there are a number of effects that can cause deviation from theory. QD alloy disorder is a potential cause of reduced symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to the structures with C 2v sym metry, in quantum dots with C 3v symmetry, the aniso tropic doublet splitting is forbidden [7,8]. In a number of works, the authors observed a very small (Շ10 μeV) anisotropic splitting in the [111] quantum dots imme diately after the growth (without further treatment) [9][10][11][12], as well as the generation of entangled photon pairs [13,14].…”
Section: Introductionmentioning
confidence: 94%